Research on microwave photonic channelization receiving technology based on dual coherent optical frequency comb - Bo CHEN; Yangyu FAN; Yongsheng GAO (Tongxin xuebao)
In order to meet the future development needs of broadband communications, a microwave photonic channelization receiver based on dual coherent optical frequency comb (OFC) was proposed.The used optical frequency comb can be generated by only a dual parallel Mach-Zehnder modulator (DPMZM), which not only has high degree of flatness and out band rejection ratio, flexible and adjustable free spectrum range, but also effectively simplifies the complexity of the receiver.In the I/Q demodulation module, by the balanced detection method the second-order intermodulation distortion (IMD2) and direct current (DC) offset were effectively suppressed, and the dynamic range of the receiver was improved, at the same time, the electrical hybrid couple (EHC) and electric bandpass filter (EBPF) were used to solve the problem of image interference that is common in superheterodyne architectures.Finally it achieves channelized reception of 5 GHz bandwidth RF signals.